UJI DOSIS PUPUK ORGANIK CAIR DAN BERBAGAI JARAK TANAM TERHADAP HASIL TANAMAN LOBAK (Raphanus sativus, L.) (Universitas Tidar, 2019)
A research to study Dose of Liquid Organic Fertilizer and Plant Spacing on Radish (Raphanus sativus, L.) conducted on May until July 2018, in Ngablak Village, Ngablak District, Magelang. The altitude is 1300 m, with Andosol soil, and pH of 6,8. The research method was factorial experiment (4 x 3) arranged in complete randomized block design (RCBD) with three block. The first factor was organic liquid fertilizer dose, 5, 10, 15, and 20 l/ha. The second factor was plant spacing, 45 cm x 20 cm, 45 cm x 30 cm, and 45 cm x 40 cm. The result showed increasing dose of liquid organic fertilizer gave the regular result on number of leaves, length of tuber, fresh weight of tuber, volume of tuber, fresh weight of stover, fresh weight of tuber m2, and harvest index. Plant spacing 45 cm x 40 cm resulted in highest yield on number of leaves, length of tuber, fresh weight of tuber, volume of tuber, fresh weight of stover, fresh weight of tuber m2, and harvest index. Liquid organic fertilizer dose of 9,76 l/ha and plant spacing 45 cm x 40 cm gave the fresh weight of stover 5,83 ton/ha.